Academic Culture Shock in Postgraduate Students Based on Demographical Data - Nadiya Kurniati; Lulu Fatihatul Uyun; Tran Thien Thanh Toan (Universitas Sarjanawiyata Tamansiswa, 2024)
Culture shock is a phenomenon that manifests in individuals encountering alterations in their surroundings or cultural context compared to their original environment and culture. This occurrence frequently manifests within professional, social, or academic settings. This research endeavors to elucidate the phenomenon of academic culture shock experienced by Aanvulen postgraduate students. This research methodology employs a quantitative survey approach. The participants in this study comprised active postgraduate students with diverse academic backgrounds from various departments, totaling 20 respondents from the West Java province, each having a maximum of two years of lecture attendance. The instrument employed in this study was a culture shock questionnaire comprising 16 statement items designed to identify and assess affective, behavioral, and cognitive dimensions. The analysis of data employed in this study was of a descriptive nature. The findings indicated that 60% of Aanvulen students experienced culture shock within the moderate shock category.